The Correlation of Teacher Performance and Learning Method with Learning Outcomes of Al Qur'an Hadits at Darul A’mal Metro City - Markaban, Markaban; Syafe’i, Imam; Jannah, Siti Raudlatul; Intamano, Banthita (Bulletin of Pedagogical Research, 2022)
The learning process was monotonous or less varied. This meant that the learning outcomes of students were still low, hence the learning process was less attractive to students.. This article was to apply a varied learning model that can improve student learning outcomes in the lessons of Al-Qur'an Hadith for Class X. IPA.1 Students MA Darul A'mal Metro City. The techniques collecting data used observation, questionnaires, interviews and documentation. An analysis of the data used product moment with statistical analysis techniques. From the calculation it can be seen showed that the correlation of teacher performance and learning methods to the learning outcomes of the Al-Qur'an Hadith for Class X. IPA.1 Students MA Darul A'mal Metro City, with a high correlation, namely total value of 0.811. If this value was correlated with r count = 0.811 if consulted with the value of r table, then the coefficient was a high influence, because rcount = 0.811 with db = n-2 = 22 greater than r table 5% = 0.423, or rcount = 0.811 was greater than rtable 1% = 0.537. r table 5% 0.423 smaller than r count 0.811 greater than 1% 0.537 can be written as 0.423 <0.811> 0.537. Keywords: Teacher Performance, Learning Method, Learning Outcome